Comparison of Pandemic (H1N1) 2009 and Seasonal Influenza Viral Loads, Singapore - Lee, Chun K. (Centers for Disease Control and Prevention, 2011)
Mean viral loads for patients with pandemic (H1N1) 2009 were ≈1 log(10) times lower than those for patients with seasonal influenza within the first week after symptom onset. Neither pandemic nor seasonal influenza viral loads correlated with clinical severity of illness. No correlation was found between viral loads and concurrent illness.